A textualização argumentativa de redações nota 1000 do Enem - Bruna Amarante de Mendonça Cohen (2022)
The purpose of this dissertation is to discuss the argumentation process in essays of National High School Exam (Enem), an exam of great relevance for the country. The exam’s essay evidences the importance of argumentative writing in both academic context and professional life of an individual, and, because of that, this investigation took place, and aims to be a contribution for the teaching of Argumentation based on the competences described on the exam’s mark scheme. Aiming to put in evidence how argumentative textualization processes are manifested in essays that obtained maximum grade in Enem’s 2019 edition, this research was carried out, having as its theoretical framework the Theory of Argumentation in Language by Anscombre & Ducrot (1994), also discussed by Cabral (2010) and Koch (2011), as well as the notions of authority argumentation by Ducrot (1987) and cohesive devices by Ducrot (1983), Koch (2020) and Koch & Elias (2016). The methodological basis that oriented the analysis of Enem’s essays made available by National Institute for Educational Studies and Research Anísio Teixeira (Inep) and selected as our corpus was the sequential typology by Adam (2019) from which the process of textualization of each of the texts was identified. This research results points out to the fact that the argumentation in the analysed essays is accomplished not only by argumentative sequences, but also by explanatory and descriptive sequences, that, together with the authority argumentation mechanism and the cohesive devices, compose its argumentative textualization.